The Prevalence of Frontal Cells and Their Relation to Frontal Sinusitis: A Radiological Study of the Frontal Recess Area. (24th July 2013) - Eweiss, Ahmed Z.; Khalil, Hisham S.
Abstract : Background . The frontal recess area represents a challenge to ENT surgeons due to its narrow confines and variable anatomy. Several types of cells have been described in this area. The agger nasi cells are the most constant ones. The frontal cells, originally classified by Kuhn into 4 types, have been reported in the literature to exist in 20%–41% of frontal recesses. Aim of the Study . To identify the prevalence of frontal recess cells and their relation to frontal sinus disease. Methods . Coronal and axial CT scans of paranasal sinuses of 70 patients admitted for functional endoscopic sinus surgery (FESS) were reviewed to identify the agger nasi, frontal cells, and frontal sinus disease. Data was collated for right and left sides separately. Results . Of the 140 sides reviewed, 126 (90%) had agger nasi and 110 (78.571%) had frontal cells. 37 frontal sinuses were free of mucosal disease, 48 were partly opacified, and 50 were totally opacified. There was no significant difference found in frontal sinus mucosal disease in presence or absence of frontal cells or agger nasi. Conclusions . The current study shows that frontal cells might be underreported in the literature, as the prevalence identified is noticeably higher than previous studies.